Pemanfaatan Jakaba pada Pembibitan Kakao di Kelompok Tani Plea Puli - Koten, Theresia Boleng; Bolly, Yovita Yasintha; Wahyuni, Yuyun (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Cocoa is one of the main plantation commodities in Bloro village, especially for the Plea Puli farmer group, Nita subdistrict, Sikka Regency. The very promising selling price of cocoa commodities makes people try to develop cocoa cultivation. Failure in cocoa breeding is a serious problem. The community is considered a failure because the breeding success rate is below 50%. The ability of the public to buy cocoa seeds on the market also requires quite a large amount of money. Cocoa nurseries are very necessary because nurseries aim to obtain healthy seeds and superior clones that are resistant to pests and diseases and increase yields both in quantity and quality. Therefore, assistance and development of nurseries is carried out. by utilising Jakaba. It is hoped that this activity can help the community's difficulties to contribute to the prosperity of the local community. The method used is the socialisation of materials on the benefits of Jakaba in cocoa nurseries, followed by demonstrations on making Jakaba, practices for making planting media, planting and maintenance. The results show that the community experienced seedling failures due to inappropriate planting media, and most importantly, plant nutrient needs were unmet. These factors are the main problem of nursery failure. The results of the nursery carried out in this activity reached 98% of the total seeds planted.